2015
DOI: 10.1007/s10549-015-3662-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening for germline mutations in breast/ovarian cancer susceptibility genes in high-risk families in Israel

Abstract: We evaluated the clinical utility of screening for mutations in 34 breast/ovarian cancer susceptibility genes in high-risk families in Israel. Participants were recruited from 12, 2012 to 6, 2015 from 8 medical centers. All participants had high breast/ovarian cancer risk based on personal and family history. Genotyping was performed with the InVitae™ platform. The study was approved by the ethics committees of the participating centers; all participants gave a written informed consent before entering the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
5
0
3
Order By: Relevance
“…The burden estimates are also made at the population level and, thus, do not necessarily reflect the cancer burden among subpopulations, such as people with lower socioeconomic statuses who are at a much higher risk of breast cancer mortality (Feinglass et al, 2015), or among various ethnic groups where genetic susceptibilities to breast cancer are more prevalent (Torres-Mej ıa et al, 2015;Yablonski-Peretz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The burden estimates are also made at the population level and, thus, do not necessarily reflect the cancer burden among subpopulations, such as people with lower socioeconomic statuses who are at a much higher risk of breast cancer mortality (Feinglass et al, 2015), or among various ethnic groups where genetic susceptibilities to breast cancer are more prevalent (Torres-Mej ıa et al, 2015;Yablonski-Peretz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…1 In contrast, such testing is not sufficient if there is a significant personal or family history of cancer because other nonfounder BRCA mutations, and mutations in other cancer risk-predisposition genes have been reported in the AJ population. 34,35 Stratification aligns well with best clinical practice because each participant, based on his or her initial risk level, can be offered the most appropriate genetic counseling and testing. For those with significant cancer histories, that testing often can include panels of cancer-susceptibility genes that are cost-effective and time-efficient.…”
Section: Stratification and Resulting Routine Clinical Care For Those...mentioning
confidence: 90%
“…These prevalence findings are similar to the published literature addressing this question in AJ patients (Table 4). 9,[15][16][17][18][19][20]27 Most recently, Walsh et al 20 assessed genetic testing results from 1007 women from 12 major cancer centers who were diagnosed with invasive breast cancer. This group found that 7 of the patients (0.7%) had nonfounder BRCA1/2 mutations and identified 31 patients (3%) with mutations in non-BRCA1/2 genes, the same rate identified in the current study cohort.…”
Section: Discussionmentioning
confidence: 99%